2016
DOI: 10.3389/fpls.2016.00521
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Alleviates Salt Stress Inhibited Photosynthetic Performance by Interacting with Sulfur Assimilation in Mustard

Abstract: The role of nitric oxide (NO) and sulfur (S) on stomatal responses and photosynthetic performance was studied in mustard (Brassica juncea L.) in presence or absence of salt stress. The combined application of 100 μM NO (as sodium nitroprusside) and 200 mg S kg−1 soil (S) more prominently influenced stomatal behavior, photosynthetic and growth performance both in the absence and presence of salt stress. The chloroplasts from salt-stressed plants had disorganized chloroplast thylakoids, but combined application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
157
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(176 citation statements)
references
References 82 publications
18
157
0
1
Order By: Relevance
“…Evidence suggests that NO promotes S-assimilation, which is linked to ET production through Cys synthesis [86]. Hence, it may be speculated that NO and S interact to modulate ABA and ET levels in guard cells that may inluence the stomatal and photosynthetic response under salt stress conditions.…”
Section: No-phytohormone Cross Talk Under Salinity Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that NO promotes S-assimilation, which is linked to ET production through Cys synthesis [86]. Hence, it may be speculated that NO and S interact to modulate ABA and ET levels in guard cells that may inluence the stomatal and photosynthetic response under salt stress conditions.…”
Section: No-phytohormone Cross Talk Under Salinity Stressmentioning
confidence: 99%
“…However, recent studies indicate ET as a stress-signaling hormone that interacts with signaling cascades of other phytohormones to enhance tolerance against various biotic/abiotic stresses [70,86]. Studies involving tobacco seedlings showed that transcriptional activation of ethylene response factor (ERF) in ethylene-signaling process improved salt stress tolerance by decreasing ROS accumulation [89].…”
Section: No-phytohormone Cross Talk Under Salinity Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The NO and sulfur nutrition were found to prevent chloroplasts damage in salt-exposed mustard (B. juncea) plants (Fatma et al 2016). The SNP stimulated the expression of AOX, a component of plant mitochondrial electron transport, in barrelclover (M. truncatula) under high salinity thus, alleviating oxidative stress and photosynthetic damages (Jian et al 2016).…”
Section: Activation Of Antioxidant Systemmentioning
confidence: 99%
“…Avicennia marina (Chen et al 2010) Cucumis sativus (Shi et al 2007) Cynodon dactylon (Liu et al 2016) Gossypium hirsutum (Liu et al 2013;Kong et al 2016) Kandelia obovata (Lang et al 2014) Aegiceras corniculatum (Lang et al 2014) Limonium bicolor (Ding et al 2013) Populus euphratica Triticum aestivum (Tian et al 2015) Induction of osmoregulators accumulation Brassica juncea (Zeng et al 2011;Khan et al 2012) Cicer arietinum (Ahmad et al 2016) Cucumis sativus (Fan et al 2013) Gossypium hirsutum (Liu et al 2013) Lycopersicom esculentum ) Solanum lycopersicum (Hayat et al 2012) Triticum aestivum (Tian et al 2015) Induction of polyamines accumulation Cucumis sativus (Fan et al 2013) Protection of photosynthetic apparatus Brassica juncea (Fatma et al 2016) Cicer arietinum (Ahmad et al 2016) Fragaria × ananassa (Christou et al 2014) Gossypium hirsutum (Kong et al 2016) Medicago truncatula (Jian et al 2016) Stimulation of seed germination Arabidopisis thaliana (Zhao et al 2007) Triticum aestivum (Zheng et al 2008) Zea mays (Bai et al 2011) Stimulation of plant growth Arabidopisis thaliana ) Glycine max (Egbichi et al 2014;Vaishnav et al 2016) Gossypium hirsutum and increased chlorophylls content and photosynthetic rate (Kong et al 2016). The NO and sulfur nutrition were found to prevent chloroplasts damage in salt-exposed mustard (B. juncea) plants (Fatma et al 2016).…”
Section: Activation Of Antioxidant Systemmentioning
confidence: 99%